Britain's identity crisis [biometric ID cards]. - Guizzo, E. (IEEE spectrum)
To help in its fight against fraud, illegal immigration, organized crime, and terrorism, the British government proposed the issuance of a national identity card and an accompanying identity verification database system. The card-database combination is expected to provide a foolproof identify check for every person living in the UK. There are, however, several organizations such as the London School of Economics and Political Science (LSE) who are critical of the initiative for lacking well-defined goals and for its high cost. They claim that the design of the system is based on unreliable and inadequate technologies that could result in privacy and security problems. The LSE suggests an alternative method based on a distributed approach, which eliminates the need for a central identity verification system. The verification would instead only take place locally, making it simpler to implement and radically cheaper. As supporters and critics further scrutinize the ID cards' proposed legislation, the debate continues in Parliament.